Program Ekonomi Kreatif Berbasis Ethnobotany untuk Pemberdayaan Masyarakat Gampong Cot Kunyet, Kecamatan Padang Tiji, Kabupaten Pidie - Lasri Lasri; Erna Fitriani Hamda; Saprijal Saprijal; Ridayani Ridayani; Saddam Saddam; A’zizah A’zizah; Ida Tutia Rakhmi; Muhammad Safwan Jamil (Pusat Riset dan Inovasi Nasional, 2025)
The creative economy program is one of the government's efforts to encourage economic sectors based on creativity and innovation (1). One sub-sector that is receiving increasing attention is the development of products based on local culture and natural resources, such as Ethnobotany products. This community service program was implemented with the aim of increasing the independence and welfare of the Cot Kunyet Village community, Padang Tiji District, Pidie Regency through the development of an ethnobotany-based creative economy. The potential of local plants in this area is very abundant and has high economic value, but so far has not been optimally utilized. Through this activity, the community is provided with the understanding and skills to process various types of local plants into value-added products by utilizing local expertise and simple technology. The implementation method includes field observation, socialization of the creative economy concept, training in processing natural materials, production assistance, and digital marketing strategies. The training was carried out with participatory community involvement, especially groups of housewives and village youth. Some of the products produced include herbal soap, aromatherapy oil, spice powder drinks, and crafts made from local plants. In addition to improving technical skills, this activity also introduced the concept of packaging design and marketing through e-commerce platforms to expand market reach. The program's implementation results demonstrate an increase in community capacity, creativity, and motivation in developing businesses based on local potential. The community is beginning to understand the importance of sustainable and economically valuable natural resource management. Furthermore, this activity strengthens a sense of community and raises awareness of the importance of preserving traditional knowledge. Overall, the program has had a positive impact on increasing community capacity and opening up new opportunities for developing a creative, innovative, and competitive local economy